Strains in Offshore US Dollar Funding during the COVID-19 Crisis : Some Observations - Barajas, Adolfo; Deghi, Andrea; Fendoglu, Salih; Xu, Yizhi (Washington, D.C. : International Monetary Fund, 2020)
This note analyzes recent trends in offshore US dollar funding markets and explores the drivers of dollar funding costs during the COVID-19 pandemic crisis. Preliminary evidence suggests that only part of the sharp increase in observed dollar funding costs can be attributed to the standard supply- and demand-side factors analyzed in the October 2019 Global Financial Stability Report (GFSR), including the dollar funding fragility of non-US global banks. Changes in market structure since the global financial crisis, as well as heightened uncertainty and tensions in the commercial paper market, may provide further explanations for the movements in dollar funding costs in late March 2020. The US Federal Reserve's swap line arrangements have helped lessen strains in dollar funding markets, but funding pressure remains significant for some emerging market economies, notably those with-out access to the swap lines. Furthermore, tighter dollar funding conditions appear to have accompanied increases in financial stress in the home economies of affected non-US global banks and to have generated adverse spill-over effects in the form of cutbacks in cross-border lending.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet